CAPACITY ANALYSIS OF SINGLE PILE BEARING CAPACITY BASED ON STATIC METHOD AND N-SPT TEST ON PILE DRIVING ANALYZER TEST (CASE STUDY OF PT. ASAHI FORGE INDONESIA PHASE II PROJECT) - Aseanto Resi (NAROTAMA UNIVERSITY, Indonesia, 2019)
Soil investigation has an important role before building a building. The carrying capacity of the soil obtained from the results of soil investigations is very influential on the shape and dimensions of the foundation itself. In the PT.Asahi Forge Indonesia Project, the SPT test data is out of sync with the actual piling results related to embedded pile penetration. The design plan for piles with a length of 7 m based on the N-SPT test turned out that in the field, the piles achieved a bearing capacity at a depth of 9 meters. The final project aims to analyze and compare the carrying capacity of a single pile based on static methods and N-SPT test on the Pile Driving Analyzer. The method used in this research is the study method of laboratory test results and N-SPT. Work steps include; preparation, literature study, data collection, carrying capacity analysis, and comparison of analysis results. The results of the analysis of the carrying capacity of the piles based on the static method by the (Vijayvergiya & Focht, 1974) method amounted to 549,201 kN; The (McClelland, 1974) Method of 426,292 kN; The U.S Army Corps Method is 459,545 kN and the Tomlinson (1977) Method is 474,191 kN. While the results of N-SPT were bearing piles bearing capacity with the Mayerhof (1956) method of 738,645 kN and the Schmertmann (1967) Method of 451,327 kN. Based on these results, the N-SPT test based on the Mayerhof (1956) Method of 738,645 kN was the closest to the PDA test results of 755,116 kN. The comparison of the results of the analysis between the static test, N-SPT and PDA test is 19: 24: 30. This means that the carrying capacity of the static pile and PDA test has a difference of 37% while between the N-SPT and PDA test has a difference of 20%.